Thrombospondin 2 Promotes IL-6 Production in Osteoarthritis Synovial Fibroblasts via the PI3K/AKT/NF-κB Pathway - Hou CH; Tang CH; Chen PC; Liu JF (Dove Medical Press, 2021)
Chun-Han Hou,1 Chih-Hsin Tang,2- 5 Po-Chun Chen,5- 7 Ju-Fang Liu7,8 1Department of Orthopedic Surgery, National Taiwan University Hospital, Taipei City, Taiwan; 2School of Medicine, China Medical University, Taichung, Taiwan; 3Graduate Institute of Biomedical Science, China Medical University, Taichung, Taiwan; 4Chinese Medicine Research Center, China Medical University, Taichung, Taiwan; 5Department of Biotechnology, College of Health Science, Asia University, Taichung, Taiwan; 6Translational Medicine Center, Shin-Kong Wu Ho-Su Memorial Hospital, Taipei City, Taiwan; 7Department of Medical Research, China Medical University Hospital, China Medical University, Taichung, Taiwan; 8School of Oral Hygiene, College of Oral Medicine, Taipei Medical University, Taipei, TaiwanCorrespondence: Ju-Fang Liu; Po-Chun ChenSchool of Oral Hygiene, College of Oral Medicine, Taipei Medical University, No. 250 Wu-Hsing Street, Taipei, 11031, TaiwanTel +8862-27361661 Ext. 5110Email jufangliu@tmu.edu.tw; blibra1002@gmail.comBackground: It is known that osteoarthritis (OA) pathogenesis involves inflammation that drives pathologic changes and that the matricellular protein, thrombospondin-2 (TSP2), is involved in angiogenesis, carcinogenesis, and inflammation. However, how TSP2 contributes to OA inflammatory processes is unclear.Objective: The aim of current study was to elucidate whether TSP2 could promote interleukin-6 (IL-6), a pro-inflammatory cytokine, expression in osteoarthritis synovial fibroblasts (OASFs).Methods: The synovial fibroblasts isolated from osteoarthritis and healthy donors were incubated with recombinant TSP2 to evaluate its effect in OA pathogenesis. The SFs were incubated with recombinant TSP2, followed by determining the IL-6 expression by qPCR and Western blot. After SFs were incubated with TSP2 for different time interval, the Western blot was performed to investigate the activation of signal pathway. The different strategies including neutralizing antibodies, siRNAs, and chemical inhibitors were used to discover the signal transduction in response to TSP2 incubation in OASFs. To evaluate the therapeutic potential of TSP2 in osteoarthritis, the anterior cruciate ligament transection (ACLT) in SD rats was performed in the presence or absence of TSP neutralizing antibody treatment.Results: Our investigations have revealed that TSP2 promoted IL-6 expression in OASFs in a dose-dependent manner, especially in 30 and 100 ng/mL concentration (p < 0.05). Using different strategies including neutralizing antibodies, siRNAs, and chemical inhibitors, all of which attenuated signal pathway components in OASFs, we found evidence for the involvement of integrin αvβ3, PI3K, Akt, and NF-κB in TSP2-mediated upregulation of IL-6 (p < 0.05). Finally, in the result of rat ACLT surgical model, we found that TSP2 neutralizing antibody had protective effects in cartilage destruction during OA progression.Conclusion: Thrombospondin-2 palys an important role in osteoarthritis pathogenesis and provides an opportunity to deal with osteoarthritis.Keywords: TSP2, osteoarthritis, integrin αvβ3, IL-6